2007
DOI: 10.1002/prca.200600669
|View full text |Cite
|
Sign up to set email alerts
|

Protein profiling of oral brush biopsies: S100A8 and S100A9 can differentiate between normal, premalignant, and tumor cells

Abstract: In oral mucosa lesions it is frequently difficult to differentiate between precursor lesions and already manifest oral squamous cell carcinoma. Therefore, multiple scalpel biopsies are necessary to detect tumor cells already in early stages and to guarantee an accurate follow-up. We analyzed oral brush biopsies (n = 49) of normal mucosa, inflammatory and hyperproliferative lesions, and oral squamous cell carcinoma with ProteinChip Arrays (SELDI) as a non-invasive method to characterize putative tumor cells. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 56 publications
1
19
0
Order By: Relevance
“…From our current findings, reduced levels of S100A8/A9 and resulting loss of function de-regulates growth in SCCs and would contribute to carcinogenesis. S100A8/A9 levels are generally low or not detectable in squamous carcinoma cells, whereas in inflammatory or hyperproliferative oral lesions and HNSCC tissues, S100A8/A9 complex is markedly down-regulated at both mRNA and protein levels compared to normal mucosa [31], [32]. Consistent with these findings, we found that HNSCC show approximately 10-fold lower S100A8 and S100A9 gene expression than NAT.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…From our current findings, reduced levels of S100A8/A9 and resulting loss of function de-regulates growth in SCCs and would contribute to carcinogenesis. S100A8/A9 levels are generally low or not detectable in squamous carcinoma cells, whereas in inflammatory or hyperproliferative oral lesions and HNSCC tissues, S100A8/A9 complex is markedly down-regulated at both mRNA and protein levels compared to normal mucosa [31], [32]. Consistent with these findings, we found that HNSCC show approximately 10-fold lower S100A8 and S100A9 gene expression than NAT.…”
Section: Discussionsupporting
confidence: 86%
“…S100A8/A9 protein expression is reduced in HNSCC as reported previously [31], [32]. In this study, we compared the expression of S100A8 and S100A9 subunit genes in matching HNSCC and normal adjacent (NAT) tissues using real-time quantitative reverse-transcription polymerase chain reaction (qRT-PCR).…”
Section: Resultsmentioning
confidence: 80%
“…S100A8 is also involved in the metastatic process, acts as chemoattractant for the homing of tumor cells to premetastatic sites, and increases the motility of circulating cancer cells. In two of our previous studies with microdissected cancer tissue (Melle et al 2004) and brush biopsies from oral cancer (Driemel et al 2007) analyzed by SELDI, we showed an explicit and significant stepwise loss of expression of S100A8 during the progression from normal to proliferative/inflammatory and finally to cancer cells. A reason might be the observation that S100A8 and S100A9 have partly antagonistic functions depending on whether they act alone or in a Ca 21 -dependent heterocomplex.…”
Section: Discussionmentioning
confidence: 92%
“…Melle and co-workers demonstrated that calgranulin A and calgranulin B were detectable in protein lysates from positive areas and were absent in the negative areas of pharyngeal squamous tumour epithelial cells, using ProteinChip arrays [20]. Driemel and colleagues showed that S100A8 and S100A9 can differentiate between normal mucosa, inflammatory and hyperproliferative lesions, and oral squamous cell carcinoma with a sensitivity of 100% and specificity of 91% using SELDI-ToF [21].…”
Section: Discussionmentioning
confidence: 99%